Impact of Matrix Metalloproteinases 2 and 9 and Tissue Inhibitor of Metalloproteinase 2 Gene Polymorphisms on Allograft Rejection in Pediatric Renal Transplant Recipients - Akad Dincer, Selin; Sahin, Feride Iffet; Terzi, Yunus Kasim; Gulleroglu, Kaan; Baskin, Esra; Haberal, Mehmet (Experimental and clinical transplantation, 2023)
Acute and chronic allograft rejection have been continuously an important obstacle in the follow-up of renal transplant recipients. During clinical management, several factors acting simultaneously result in acute rejection and chronic allograft nephropathy. Matrix metalloproteinases and tissue inhibitors of metalloproteinases are responsible for the organization of the extracellular matrix and play roles in cell proliferation and cellular invasion. Changes in matrix metalloproteinase expression levels have been reported to be associated with renal allograft rejection and interstitial fibrosis. In this study, we aimed to investigate functional polymorphisms of MMP2, MMP9, and TIMP2 genes in pediatric renal transplant recipients. Our study included 68 kidney transplant recipients and 58 control patients. The kidney transplant recipient group was further divided into 2 subgroups: no graft rejection (n = 47) and graft rejection (n =21). MMP2 -735C >T (rs2285053), MMP2 -1306C >T (rs243865), MMP2 -1575G >A (rs243866), MMP9 c.-1562C >T (rs3918242), TIMP2 -418G >C (rs8179090), and TIMP2 303C > T (rs2277698) polymorphisms were analyzed with the use of polymerase chain reaction and restriction fragment-length polymorphism methods. Allele prevalence was compared with reference values of the control group, and Hardy-Weinberg equilibrium was tested. Mean ages were 16.7 ± 3.9 years for the study group and 14.8 ± 5.6 years for the control group. The mean follow-up time after transplant was 37.7 ± 7.9 months. We compared allele frequencies in the 2 groups and calculated a statistically significant difference in rs2285053, rs243865, rs243866, rs3918242, rs8179090, and rs2277698 polymorphism frequencies between the transplant recipients and control patients. When the transplant recipient group was compared in itself with regard to allograft rejection, all investigated polymorphisms except TIMP2 -418G >C (rs8179090) revealed a statistically significant difference between those with and without rejection (P < .05). Matrix metalloproteinases and their tissue inhibitors could be important predictive biological markers for the follow-up of kidney transplant recipients.